1971
DOI: 10.1111/j.2042-7158.1971.tb08694.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of preservatives with cetomacrogol

Abstract: The interaction of a number of commonly used preservatives (benzoic acid, p‐hydroxybenzoic acid, methyl p‐hydroxybenzoate, propyl p‐hydroxybenzoate and chloroxylenol with the non‐ionic surfactant cetomacrogol was examined and a comparison made of various methods of expressing this interaction. It is suggested that the Scatchard equation is the most satisfactory equation for describing the binding data. Binding parameters determined from a Scatchard plot in the concentration range of free preservative appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1971
1971
1978
1978

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Binding parameters determined from a Scatchard plot in the concentration range of free preservative necessary for antimicrobial activity were used to calculate the total concentration of preservative needed in the surfactant system (17). Tests of the inactivation of preservatives by the added anion-active surfactants showed that inactivation occurred only after a certain ratio of surfactant to preservative concentration was reached.…”
Section: General Pharmacymentioning
confidence: 99%
“…Binding parameters determined from a Scatchard plot in the concentration range of free preservative necessary for antimicrobial activity were used to calculate the total concentration of preservative needed in the surfactant system (17). Tests of the inactivation of preservatives by the added anion-active surfactants showed that inactivation occurred only after a certain ratio of surfactant to preservative concentration was reached.…”
Section: General Pharmacymentioning
confidence: 99%
“…Vários aut verificaram diminuicão da atividade antimicrobiana dos conservantes e, procura mostrar que ocorre a interação dessas substâcias com as macromoléculas, tanto tensoativo quanto do agente suspensor. (19,85,86,91,144) Compor uma fórmula medicamentosa requer estudo criterioso dos componentes. Aqueles que ainda hoje acreditam que formular é uma arte, escolhem adjuvantes por meio de conhecimentos adquiridos da literatura, por suas experiên pessoais e criatividade.…”
Section: Capítulo 1 Introduunclassified
“…Kazmi and Mitchell (1) compared various methods of expressing the interaction of a number of commonly used preservatives with the nonionic surfactant cetomacrogol and found that protein binding equations such as Eq. 1 could be used to describe the binding data:…”
mentioning
confidence: 99%